Diversifikasi Pemasukan Dunia Perbankan Syariah Indonesia : Resiko Dan Kinerja - Aprilia, Cindy Ayu; Harris, Allan; Handayani, Agustia (Sekolah Tinggi Ilmu Ekonomi Syariah (STIES) ALIFA, 2024)
The aim of this research is to examine the impact of income diversification on the risk and performance of state-owned banks due to structural changes in the banking sector in Indonesia. In Indonesia, there has been a transition from traditional intermediaries (loans financed by deposits) to offering interest-free income. Income diversification has a negative impact on the performance of state-owned banks. These state-owned banks often do not pursue strategies outside their core business, because owners see fluctuations in profits as a threat to their ability to control. Company size and debt ratio are used as control variables. The results of this research show that the larger the company size, the lower the ROA will generally be. This suggests that large banks may have difficulty achieving high ROA due to more complex operations. The higher the ratio of Loans to Total Assets (LTA), usually the ROA is also higher. This may indicate that banks that are more aggressive in distributing credit are relatively more efficient in generating income.